The Effect Of Individual Characteristics, Business Characteristics, Loan Characteristics, And Religious Awareness On Borrowers’ Loan Repayment Ability: A Case Study At Pt. Bank Rakyat Indonesia (Persero) Tbk. Palopo Branch Office - Rusdi Rusdi; Ahmad Syarief Iskandar; Ishak Ishak (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of individual characteristics, business characteristics, credit characteristics, and religious awareness on borrowers' loan repayment ability at PT Bank Rakyat Indonesia (Persero) Tbk. Branch Office Palopo, particularly BRI Unit Bua. A quantitative approach with a correlational design was employed. The study involved 60 borrowers selected through purposive sampling. Data were collected using questionnaires, observations, and documentation and analyzed using binary logistic regression with IBM SPSS Statistics version 32. The results indicate that business turnover, business experience, loan repayment period, and religious awareness significantly affect borrowers' loan repayment ability. Meanwhile, the number of dependents, educational level, and loan amount have no significant effect. Business experience is the most dominant factor influencing loan repayment ability. In addition, religious awareness positively affects borrowers' ability to fulfill their financial obligations. These findings are expected to provide useful insights for banks in improving credit assessment and credit risk management for MSME financing